ANALYSIS OF FACTORS RELATED TO THE INCIDENT OF DIARRHEA IN TODDLERS AT THE AR RAHMAN CLINIC IN 2023 - Aisyah, Syahratul Siti; Sahrudi, Sahrudi (HEARTY, 2025)
Background : Diarrhea is a disease that causes feces to come out more than 3 times with a liquid consistency that can contain blood or mucus and a frequency that occurs more often than normal (World Health Organization, 2019). Diarrhea is an endemic disease with the potential for Kejadian Luar Biasa (KLB). which is often accompanied by death in Indonesia. The eastern group with the highest prevalence of diarrhea (based on diagnosis from health workers) is in the 1-4 year age group at 11.5% and in infants at 9%. The coverage of diarrhea findings in toddlers in Bali province amounted to 37.3% in 2019. The prevalence of diarrhea in West Java province according to characteristics based on Riskesdas 2018 was recorded as 1,286 (10.40%) children with diarrhea in the age group < 1 year, 5,312 (13.43% ) children with diarrhea aged 1-4 years, 12,806 (6.98%) na with diarrhea group. The number of diarrhea sufferers found and treated in Karawang in 2018 was 57,682 cases (29,869 male sufferers and 27,813 female sufferers) or 94.82%. The diarrhea rate in Karawang Regency is 48/1000 population.research purposes: This is a problem for the child's health level because the factors that trigger diarrhea in toddlers are the knowledge/agent, environment and behavior of the mother or family itself.Methods: This type of research is quantitative analytical descriptive using a descriptive correlation design with a cross-sectional approach where the research instrument uses a questionnaire. The sample for this study was mothers with toddlers aged 1-4 years who came for treatment at the Ar Rahman clinic. The sampling technique uses a questionnaire. Data analysis carried out was univariate analysis and bivariate analysis using the Chi-Square Test.Research Results: results with a total of 80 respondents that Knowledge/Agent on the incidence of Diarrhea, the P Value of respondents is 0.024 <0.05, while for Environmental Factors the P Value of respondents is 0.000 <0.05, and for Behavior factors the P Value is 0.000 <0.05. respondents is 0.000 <0.05.Conclusions and suggestions: the factors that can cause diarrhea are the environment, knowledge and behavior, for health facilities to carry out health education, socialization, and apply Health Care to families in order to increase knowledge, behavior and a healthy environment